The influence of the specifics of small businesses on innovation:: A multiple case study of the Brazilian metal-mechanical industry (REGE Revista de Gestão, 2018)
Purpose – Based on a multi-case analysis of small businesses in the metal-mechanical industry in the region of Sorocaba, State of São Paulo, Brazil, the purpose of this paper is to analyze how small businesses (in terms of the owner, business, and influences exerted by the environment) influence innovation. Design/methodology/approach – Six case studies are used to analyze the Brazilian metal-mechanical industry. The data are collected through semi-structured interviews and direct observations. In addition, innovations over the previous five years are evaluated in order to establish a comparative pattern between companies. Findings – This study examines how facilitating factors are related to the owners of small businesses. These factors include owners’ personal ambitions, the centralization of decisions, and their confidence in their ability to make effective decisions. Factors related to the organization that favor innovation include a simple and streamlined structure and fewer levels of bureaucracy, whereas low capital intensity limit innovation. While some factors related to the environment favor innovation, others have a limiting effect (e.g. short-term horizons and a lack of formal strategic planning). Originality/value – The main contribution of this research is to show that innovation is not synonymous with financial investment. Strategic reorganization and the rationalization of productive resources through competitive priorities may lead to innovation in different spheres, helping to increase the competitiveness and strength of the national economy.